Advances in systemic lupus erythematosus. (January 2022) - Abida, Rym; Yeoh, Su-Ann; Isenberg, David A.
Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a heterogeneous course and systemic involvement. It is the result of a complex pathogenic pathway that culminates in autoantibody formation. The interaction between environmental triggers and genetic susceptibility is key in this process. Genome-wide association study technology has allowed the recognition of >80 loci associated with SLE that lead to the formation of key proteins, each contributing a small increase to the risk. Advances in the management of the disease include new validated standardized tools to capture disease activity, damage and quality of life, for clinical and research purposes. The prognosis of SLE has much improved in the last 50 years because of better general management and specific treatment, including better use of immunosuppressive agents and development of a new group of drugs – biologic therapies.